Teaching surgical skills in obstetrics and gynaecology using cadaver simulation: an innovative teaching learning method - Gaikwad, Nandkishor B.; Bhalerao, Pradnya; Maner, Tabssum; Mule, Vidya D. (International Journal of Research in Medical Sciences, 2017)
Background: Transfer of knowledge from teachers to students traditionally occurs in one direction using blackboards, overhead projectors, power-point presentations and lectures. It has many disadvantages. The main challenge in medical education is to teach surgical skills. For the learning of critical interventions, simulation-based training is structured so that the acquisition of new skills does not harm patients. Thus, the objective of this study was to enhance and improve procedural skills of resident doctors of Obstetrics and Gynaecology department of Government Medical College, Miraj using cadaver simulation in doing abdominal hysterectomy. Methods: Second year resident doctors from Obstetrics and Gynaecology department of GMC, Miraj who had completed their first year successfully in terms of basic orientation regarding surgical procedures were taken for study purpose. They were divided in two groups randomly. The first group underwent conventional method of teaching to learn the abdominal hysterectomy procedure and underwent feedback from them regarding the conventional teaching learning method. Then they were allowed to perform the procedure on a live patient and their performance of procedural skill was assessed by DOPS. (Direct observation of procedural skills). The second group underwent innovative method of use of cadaver simulation for the abdominal hysterectomy procedure and feedback on the same. They were allowed to perform the procedure on a live patient and their performance of procedural skill was assessed by DOPS. (Direct observation of procedural skills). All data was collected, analysed and processed to study the outcome of research project. Results: In group B, all resident were fully satisfied with newer method of teaching and learning for abdominal hysterectomy as surgical procedure. As far as, the advantages and disadvantages of teaching and learning are concerned, all residents pointed out large number of disadvantages in the conventional method. Evaluation of the surgical procedural skill was done by DOPS by senior faculty members of the department as per the questionnaire which showed good performance from group B. Conclusions: The benefit of simulation based medical education (SBME) is that it offers both learners and patients a safe environment for practice and error. In addition, SBME can provide a learning cycle of debriefing and feedback for learners as well as assessment and certification for procedures and competency.